Perioperative Surgical Recommendations in Patients with Lupus - Donovan Diego Ruiz Baltazar; Mariana García Morales; Julie Rosario Guadalupe Barruquin; Jocelyn Anaid Landeros Fraire; Francisco Javier Delgado Dávalos; Sergio González Ramírez; José Raúl Rodríguez Amparán; Ernesto Fernando Montelongo Sedano; José Manuel Villafuerte Hernández; Ana Denisse Aboytes Bucio; Carlos Mario González García; Doryan Monroy Cordoba (International Journal of Medical Science and Clinical Research Studies, 2024)
Systemic lupus erythematosus (SLE) is a long-lasting autoimmune condition that affects the connective tissues and has a varied and diverse range of symptoms. The severity of the disease varies greatly, with the majority experiencing less severe versions. However, it may be life-threatening depending on the extent of organ involvement. The ailment was identified as early as the Middle Ages, with the 12th-century physician Rogerius being the first to use the name lupus to describe the characteristic malar rash. In 1872, Moric Kaposi was the first to acknowledge the systemic aspect of the disease. During the perioperative period, systemic lupus erythematosus (SLE) may provide significant difficulties for the anesthesiologist due to the presence of accumulated organ damage, coagulation abnormalities, and intricate care protocols. This article focuses on the signs and therapies of adult systemic lupus erythematosus (SLE) that are relevant to anesthesiologists. It also discusses the perioperative care of these patients, who present unique challenges due to the complexity of their condition.